2010
DOI: 10.1007/s10457-010-9362-3
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a water content reflectometer and soil water dynamics for an agroforestry practice

Abstract: Water content reflectometers allow temporal and continuous assessment of spatial differences in soil water dynamics. We hypothesized that volumetric soil water content estimated by the water content reflectometers (CS616 Campbell Sci. Inc., Logan, UT) is influenced by clay content and temperature and therefore site-and or soil-specific equations are required for accurate estimations of soil water. Objectives of the study were to develop calibration equations and to evaluate soil water dynamics for an agrofores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 31 publications
3
38
0
2
Order By: Relevance
“…Western and Seyfried (2005) reported the WCR to be significantly influenced by temperature at high water contents. Similar results can be found in Stangl et al (2009) and Udawatta et al (2011). Francesca et al (2010 and Arsoy et al (2013) confirmed that WCRs were impacted by bulk electrical conductivity and temperature to a greater extent than by dielectric relaxation.…”
supporting
confidence: 89%
“…Western and Seyfried (2005) reported the WCR to be significantly influenced by temperature at high water contents. Similar results can be found in Stangl et al (2009) and Udawatta et al (2011). Francesca et al (2010 and Arsoy et al (2013) confirmed that WCRs were impacted by bulk electrical conductivity and temperature to a greater extent than by dielectric relaxation.…”
supporting
confidence: 89%
“…Undisturbed soil samples of sufficient dimensions to insert a TDR probe were also extracted from each soil layer (two samples per layer). Progressive drying was measured simultaneously by TDR and by weighing, so that a calibration equation was available for each soil layer, following a protocol adapted from Udawatta et al (2011). The volumetric soil water contents were then multiplied by the thickness of the soil layers in which each TDR probe was inserted to calculate the soil water content of each layer.…”
Section: Soil Water Contentmentioning
confidence: 99%
“…Others factors may influence on period measurements by means CS616 sensor, especially the clay content (Udawatta et al, 2011;Ojo et al, 2015). We observed that the soil moisture instrument calibrations developed by the manufacturers for a general proposing are not always adaptable for use under field conditions.…”
Section: Resultsmentioning
confidence: 95%
“…The procedures in this work were adapted by the methods proposed by Benson & Wang, (2006) and Udawatta et al (2011). At the experimental field of UNEMAT, Tangará da Serra Campus, deformed soil samples were collected at November of 2016, in subsequent layers: 0.0-0.2 and 0.2-0.4 m to represent the soil profile.…”
Section: Methodsmentioning
confidence: 99%